Evaluating autobiographical skills and their relationship with suggestibility in children: development and validation of the Children Recalling Autobiographical Memory - Vagni, Monia; Giostra, Valeria; Simione, Luca (Frontiers in Psychology, 2024)
Introduction Autobiographical narrative skills and resistance to suggestibility factors are central aspects in children’s testimony. While the assessment of suggestibility relies on standardized questionnaire, no such an instrument exists to reliably assess autobiographical skills in children. This aspect is further important when considering that the development of such skills seems to be related to the suggestibility, that is, suggestibility would be reduced in presence of higher autobiographical skills. However, no direct test of this relationship is available in literature, also due to the lack of quantitative instruments for assessing autobiographical skills. Methods To fulfill both these methodological and theoretical issues, in this study a new tool was validated to measure the main autobiographical narrative skills (Where, What, When, Who, and How) in relation to both Retrospective Memory and Prospective Memory: the Children Recalling Autobiographical Memory (CRAM). We recruited a sample of 321 children aged 7–16 years. Results and discussion The result of the EFA analysis showed one-factor model, and revealed also good fit indexes and internal reliability. After validating this new tool, we further used it to test our main hypothesis, that is, children with higher autobiographical memory skills were less vulnerable to interrogative suggestibility as assessed by Gudjonsson Suggestibility Scale 2 (GSS2). A hierarchical linear regression model showed a reduction in suggestibility with age and level of autobiographical skills. Moreover, the level of such skills moderate the effect of age, such as only in presence of high or moderate level of autobiographical skills the age significantly reduces the level of suggestibility.